The Effects of Person-Organisation Fit and Employee Commitment. The Mediating Role of Organisational Culture. - Fobi Kontor, Maxwell (Archives of Business Research, 2019)
The concept of organizational culture is significant in the study of organizational behaviour and has increasingly become a vital area of interest in academic research. Organization culture recognizes the contributions of the employees in an organization, and provides holistic understanding of what is to be achieved, how goals are interrelated, and how each employee could attain organizational goals. Organizational culture is an important factor used to determine how well an employee fits into their organizational context, and it has been asserted that a good fit between the employee and their organization is vital for organisational success. The main purpose of the study was to examine the effects of organisational culture on person organisation fit and employee commitment. Simple random sampling technique was adopted to gather responses from the respondents. The study revealed that organisational culture has a positive and significant effect on person organisation – fit and employee commitment. Moreover, it was identified that organisational culture fully mediates on person organisation-fit. Based on this, the study recommended that organizational policies regarding culture should be clear for understanding by the employees. Along this line, organization should have a flexible culture and top management should use decentralized technique of management so that employees at low level have authority and power to make decision regarding problem they encounter at their level of authority.